Axial-flexural interaction diagram of RPC columns reinforced with steel fibres. (June 2019) - Al-Tikrite, Ahmed; Hadi, Muhammad N.S.
Abstract: This paper presents analytical modelling of the axial-flexural behaviour of Reactive Powder Concrete (RPC) columns reinforced with and without steel fibres of different types (industrial and waste) in individual and hybrid forms. An analytical stress-strain model for unconfined RPC was used for the analysis of the axial loads and bending moments of the fibrous RPC columns. The layer-by-layer numerical integration method was used to calculate the axial load and bending moments in this study. The analytically developed axial load-bending moment ( P-M ) interaction diagrams were validated by using experimental results from the literature. A parametric study was carried out to investigate the influence of the properties of steel fibres on the axial-flexural behaviour of fibrous RPC columns. It was found that the analytical unconfined stress-strain model used in this study well estimates the maximum axial loads and the maximum bending moments of the RPC columns reinforced with and without different types of steel fibres. Also, the influence of the properties of steel fibres is more pronounced at eccentric and flexural loadings.